Toxicity and Bioaccumulation of Lead (Pb) in the Marine Bivalve Geloina expansa (Journal of Environmental Microbiology and Toxicology, 2025)
Heavy metal pollution is a major environmental concern due to its persistence, toxicity, and ability to bioaccumulate in aquatic ecosystems. In Malaysia, increasing attention has been given to monitoring heavy metals in local marine organisms, as their accumulation in sediments and biota threatens ecosystem health and food safety. Bivalves serve as effective bioindicators, and LC50 provides essential insight into the acute toxicity of heavy metals across species. This study investigated the effects of lead (Pb) exposure on the bivalve Geloina expansa through a 96-hour acute toxicity assay. Mortality increased with rising Pb concentrations, accompanied by higher Pb accumulation in soft tissues. The 96-hour LC50 for G. expansa was calculated as 218.23 mg/L. Exposure to 250 mg/L Pb resulted in substantial Pb accumulation (1653 ± 177.51 mg/kg) compared to controls (13.00 ± 1.04 mg/kg), confirming effective uptake. These findings highlight Geloina expansa sensitivity to Pb and its suitability for pollution monitoring.
Keywords: Geloina expansa; Lead; Toxicity; LC50; Bioaccumulation